Benthic macroinvertebrate response to water quality in three rivers of Eastern Ontario. - Dean, Stuart L. (University of Ottawa (Canada), 2000)
The benthic macroinvertebrate response to water quality changes was examined in riffle zones of three Eastern Ontario Rivers (Ottawa River, Rideau River and Jock River) during the spring and summer of 1995 and 1996. Water quality gradients were detected within the rivers but these were weakly correlated to invertebrate benthos structure making it impossible to predict one from the other. However, the observed differences in water quality among sites and rivers, although significant, may not provide a large enough water quality gradient to observe a strong signal with the invertebrate data. A principal component analysis on the invertebrate densities revealed that invertebrate variability was greater between seasons than between years. May--June samples tended to have higher variability than July--August samples. These results support a standardized approach to the macroinvertebrate sampling period from year to year and the need to sample during a less variable time of the year such as late summer or early fall. Some of the inherent problems with benthic invertebrate indices are examined and the appropriateness of a coarse taxonomic level are discussed. In general, I found no evidence of strong impacts of water quality on the benthos structure of the three rivers. However, at certain locations where water quality parameters were unusually high particularly compared to the guideline, we observed an increase in invertebrate abundance. This study does provide a reference point for each of our large rivers, from which we can compare to future monitoring work.
Keywords: Biology, Ecology.